2019
DOI: 10.1038/s41467-019-11357-9
|View full text |Cite
|
Sign up to set email alerts
|

Ancient DNA from the skeletons of Roopkund Lake reveals Mediterranean migrants in India

Abstract: Situated at over 5,000 meters above sea level in the Himalayan Mountains, Roopkund Lake is home to the scattered skeletal remains of several hundred individuals of unknown origin. We report genome-wide ancient DNA for 38 skeletons from Roopkund Lake, and find that they cluster into three distinct groups. A group of 23 individuals have ancestry that falls within the range of variation of present-day South Asians. A further 14 have ancestry typical of the eastern Mediterranean. We also identify one individual wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 74 publications
(59 reference statements)
0
8
0
Order By: Relevance
“…A prime example of this is Roopkund Lake -a Himalayan site where hundreds of skeletal remains of unknown provenance have been found at over 5,000 meters above sea level. Harney et al 54 performed genomic analyses on 23 individuals from this site, and found that just about half of the remains were from individuals with South Asian ancestry, dated to ~800 CE. The authors concluded that they may have died while performing the Nanda Devi Raj Jat pilgrimage, suggesting that this religious practice may have existed in some form at this time in the past.…”
Section: Individual Journeys and Mobilitymentioning
confidence: 99%
“…A prime example of this is Roopkund Lake -a Himalayan site where hundreds of skeletal remains of unknown provenance have been found at over 5,000 meters above sea level. Harney et al 54 performed genomic analyses on 23 individuals from this site, and found that just about half of the remains were from individuals with South Asian ancestry, dated to ~800 CE. The authors concluded that they may have died while performing the Nanda Devi Raj Jat pilgrimage, suggesting that this religious practice may have existed in some form at this time in the past.…”
Section: Individual Journeys and Mobilitymentioning
confidence: 99%
“…This new type of qpAdm protocols, termed “rotating” protocol, has been adopted in archaeogenetics widely (see, e.g., Skoglund et al 2017, Harney et al 2019, Narasimhan et al 2019, Olalde et al 2019, Calhoff et al 2021, Fernandes et al 2021, Librado et al 2021, Allentoft et al 2022, Bergström et al 2022, Lazaridis et al 2022, Oliveira et al 2022, Taylor et al 2023). The most extreme version of the “rotating” protocol simply divides a set of reference populations into all possible combinations of “right” and “proxy source” subsets of certain sizes and rotates these combinations through successive qpAdm analyses.…”
Section: Introductionmentioning
confidence: 99%
“…However, analyzing ancient DNA (aDNA) poses additional difficulties due to the widely different but generally low genome coverage and postmortem damage (PMD) observed in these samples. The aDNA databases usually contain sequence data between 0.05 and 3× average genome coverage [ 10 12 ], since the sequencing of ancient samples with low endogenous DNA content is still challenging and costly. Differences in coverage and only partial overlap of genetic markers between samples can lead to significant bias when comparing the frequencies and genotype likelihoods of genetic variants, leading to uncertainties of the inferred genotype probabilities.…”
Section: Introductionmentioning
confidence: 99%